1996
DOI: 10.1210/jcem.81.6.8964884
|View full text |Cite
|
Sign up to set email alerts
|

Novel presence of luteinizing hormone/chorionic gonadotropin receptors in human adrenal glands.

Abstract: It has been well documented that a significant proportion of chronic anovulatory patients have elevated levels of dehydroepiandrosterone sulfate (DHEAS) and luteinizing hormone (LH) and normal levels of adrenocortiocotropic hormone (ACTH). We tested the hypothesis that the zones of human adrenal cortex that secrete DHEAS may contain LH/human chorionic gonadotropin (hCG) receptors. In situ hybridization showed the presence of hybridization signals representing LH/hCG receptor mRNA transcripts in the zona reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…Because androgens are secreted by the ovaries and the adrenals, and LH receptors have been identified in the zona reticularis and the deeper layer of the zona fasciculate of adrenal glands (48), it is possible that the lower LH levels induced by E 2 therapy reduced the production of T from both the ovary and the adrenals.…”
Section: Figurementioning
confidence: 99%
“…Because androgens are secreted by the ovaries and the adrenals, and LH receptors have been identified in the zona reticularis and the deeper layer of the zona fasciculate of adrenal glands (48), it is possible that the lower LH levels induced by E 2 therapy reduced the production of T from both the ovary and the adrenals.…”
Section: Figurementioning
confidence: 99%
“…The LHCGR is normally expressed mainly in the gonads; low levels of expression have been detected in the adrenal zona reticularis [16]. Adrenal LHCGR overexpression was documented in two female patients with AIMAH and LH-responsive CS; curiously, their symptoms were not associated with pregnancy [15].…”
Section: Discussionmentioning
confidence: 94%
“…Both LHR and GnRHR can be expressed in normal adrenal tissue [5,41] , but only fetal adrenal cells secreted dehydroepiandrosterone sulphate (DHEAS) following addition of LH / hCG [45,46] . Studies involving mRNA and protein expressions have shown that in certain cases of hyperaldosteronism, LHR and / or GnRHR are markedly overexpressed [5, 39 -41] ( Table 2 ).…”
Section: Overexpression and Functionality Of Lh And Gnrh Receptors Inmentioning
confidence: 99%